1993
DOI: 10.1016/0014-5793(93)80080-e
|View full text |Cite
|
Sign up to set email alerts
|

Sequence similarity of a hornet (D. maculata) venom allergen phospholipase A1 with mammalian lipases

Abstract: We have determined the sequence of a venom allergen phospholipase A~ from white-faced hornet (Dolichovespula maculata) by cDNA and protein sequencings. This protein of 300 amino acid residues (Dol m I) has no sequence similarity with other known phospholipases. But it has sequence similarity with mammalian lipases; about 40% identity in overlaps of 123 residues. Tests suggest that hornet phospholipase has weak lipase activity. Hornet venom has 3 major allergens, and another hornet allergen antigen 5 (Dol m V) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 30 publications
2
36
0
3
Order By: Relevance
“…1D). These molecular features are also observed in all the vespid PLA 1 s reported so far (27,28,38) (Fig. 1D).…”
Section: Resultssupporting
confidence: 56%
“…1D). These molecular features are also observed in all the vespid PLA 1 s reported so far (27,28,38) (Fig. 1D).…”
Section: Resultssupporting
confidence: 56%
“…It has been reported that the substrate specificities of LPL and HL are determined by the lids of the molecules (28). Guinea pig PL has a short lid and exhibits both phospholipase A 1 and lipase activities (35), and hornet phospholipase A 1 , which has only 7 amino acids in the corresponding region, has weak lipase activity (34). Thus the "phospholipase A 1 activity" of lipase family molecules may depend on the length and amino acid sequence of the lid.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that members of the lipase superfamily (35) exhibit a wide range of ratios of phospholipase A 1 to lipase activities; classical pancreatic lipases have no significant phospholipase activity, the guinea pig and coypu lipases belonging to the type 2 pancreatic lipase-related proteins, a pancreatic lipase subfamily, exhibit high phospholipase A 1 and lipase activities (36), and new members of the lipase superfamily, hornet venom phospholipase A 1 (37) and platelet serine phospholipid-specific phospholipase A 1 (38), are devoid of lipase activity. Recent development of x-ray crystallographic studies on natural and mutated lipases and PLA 2 s provided important clues to unravel how lipolytic enzymes regulate their substrate selectivities (39,40).…”
Section: Catalytic Domain Of Rat Intestinal Phospholipase B/lipasementioning
confidence: 99%